Substitusi Tepung Ubi Ungu dalam Pembuatan Kue Soes dengan Selai Buah Naga Sebagai Snack bagi Penderita Diabetes Mellitus - Arifatul Aini Asnawi; Eliska Eliska (Puslitbang Sinergis Asa Professional, 2023)
Purple Sweet Potato (Ipomea Batatas L.Poiret) is a local plant that has potential as a functional plant that riches in nutrition and active components such as anti-oxidants, anthocyanin. The purple sweet potato also has a lower index of glycemic level until it is suitable for snacks suchs as soes cake. The objective of this research is to formulate the soes cake that has the highest anthocyanin with dragon-fruit jams that are accepted organoleptically. The method of this research is true experiments by the design of Post-Test Only Control Group Design that is analyzed descriptively. This research is conducted by using three ways. There are; levels of development of products that are divided into three levels which are involved in the process of production of purple sweet potato flour, the making of soes cake, and the filling of dragon fruits. Next, it will be tested by acceptance test and the test of anthocyanins contents. The result of this research have obtained the levels of anthocyanins with the sample of 1 gram of sweet potato flour for each content and the dry-base is 113,55 mg/100 grams, the productions of soes cake are 25,63 mg/100 grams and the dragon fruit jams has the anthocyanins levels are 88,67 mg/100 grams. Based on the whole of the acceptance result of soes cake, sweet potato flour is accepted by peoples from the side of colors, flavour, textures, and taste.